Determinants of infant feeding practices among mothers living with HIV attending prevention of mother to child transmission Clinic at Kiambu Level 4 hospital, Kenya: a cross-sectional study - Naureen Andare; Sophie Ochola; Peter Chege (Nutrition Journal, 2019)
Abstract Background Human immunodeficiency virus infection and acquired immune deficiency syndrome is global pandemic with around 150,000 children infected with HIV in 2015. In Kenya, it is estimated that 11,000 children who are under 15 years old were infected. Safe infant feeding practices are the major important determinants of the prevention of mother to child transmission. The decision to breastfeed or not is considered a very tough choice for mothers living with HIV. This study assessed the infant feeding practices and its determinants among mothers living with HIV with infants 0–12 months old. Methods This was a mixed methods cross-sectional study adopting qualitative and quantitative data collection procedures. A sample of 180 systematically selected mothers living with HIV with infants 0–12 months old attending prevention of mother to child transmission clinic participated in the study. Results Exclusive breastfeeding rate was 71.4%, mixed feeding (18.2%) and replacement feeding (10.4%). Complementary feeding with continued breastfeeding rate was 63.1%. Similarly, qualitative results showed that exclusive breastfeeding was the most preferred feeding method by mothers living with HIV. Age (Adjusted Odds Ratio (AOR) 0.19; (95% Confidence Interval (CI) 0.41, 0.85; p = 0.030) and infant feeding practice knowledge (AOR 0.20; 95% CI 0.06, 0.64; p = 0.007) were determinants of exclusive breastfeeding. Education AOR 0.17; 95% CI 0.03, 0.85; p = 0.002) and occupation (AOR 3.91; 95% CI 1.24, 12.32; p = 0.020) were determinants of complementary feeding with continued breastfeeding. Conclusion Exclusive breastfeeding is attainable in this population. However, poor infant feeding practice knowledge led to non-adherence to safe infant feeding practices such as exclusive breastfeeding. Socio-demographic factors such as age, education and occupation were established as determinants of infant feeding practices among mothers living with HIV. Ministry of Health should come up with strategies on infant feeding counseling that are aligned to a local context, to allow mothers to understand the importance of recommended infant feeding options for HIV-exposed infants.